Design of multijet nozzle for cavitation erosion enhancement - Kwek, Zhi Heng (Nanyang Technological University, 2020)
Hydrodynamic Cavitation Abrasive Finishing (HCAF) is a novel internal surface finishing process which occurs under cavitation conditions. Cavitation bubbles are stimulated and its implosion result in material removal from the target workpiece. Combined with abrasive particles, this process is an effective form of surface finishing. However, the current HCAF setup could only target single channels. There is a need to develop modifications to increase the finishing capacity in channels. One such method is via the design of a multijet nozzle. A multijet nozzle is a nozzle with one inlet and numerous outlets. This project proposes a design of a multijet nozzle capable of finishing three internal channels. Experiments would be conducted to evaluate the effectiveness of the designed nozzles for both Hydrodynamic Abrasive Finishing (HAF) and HCAF. This is done by analysing changes in surface roughness parameters, Ra and Rz.